Genome-Wide Transcriptional Changes of Rhodosporidium kratochvilovae at Low Temperature - Guo, Rui; He, Meixia; Zhang, Xiaoqing; Ji, Xiuling; Wei, Yunlin; Zhang, Qi-Lin; Zhang, Qi (Frontiers in Microbiology, 2021)
Rhodosporidium kratochvilovae strain YM25235 is a cold-adapted oleaginous yeast strain that can grow at 15 °C. It is capable of producing polyunsaturated fatty acids. Here, we used the Nanopore Platform to first assemble the R. kratochvilovae strain YM25235 genome into a 23.71 Mb size containing 46 scaffolds and 8,472 predicted genes. To explore the molecular mechanism behind the low temperature response of R. kratochvilovae strain YM25235, we analyzed the RNA transcriptomic data from low temperature (15 °C) and normal temperature (30 °C) groups using the next-generation deep sequencing technology (RNA-seq). We identified 1,300 differentially expressed genes (DEGs) by comparing the cultures grown at low temperature (15 °C) and normal temperature (30 °C) transcriptome libraries, including 553 significantly upregulated and 747 significantly downregulated DEGs. Gene ontology (GO) and pathway enrichment analysis revealed that DEGs were primarily related to metabolic processes, cellular processes, cellular organelles, and catalytic activity, whereas the overrepresented pathways included the MAPK signaling pathway, metabolic pathways, and amino sugar and nucleotide sugar metabolism. We validated the RNA-seq results by detecting the expression of 15 DEGs using qPCR. This study provides valuable information on the low temperature response of R. kratochvilovae strain YM25235 for further research and broadens our understanding of the response to low temperature of R. kratochvilovae strain YM25235.